Implementasi Algoritme Modified K-Nearest Neighbor (MK-NN) Untuk Diagnosis Penyakit Anjing - Luh Putu Novita Budiarti; Nurul Hidayat; Tri Afirianto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Dog is one of the most favorite pets. Interacting with dogs has its benefit such as lowering stress levels and leading the owners to have a more active lifestyle. However, the dog's health itself should be taken care of. Dog who suffers from a disease can infect other pets or even humans, so veterinarian help is needed. Things will be difficult if the owners realize that their dogs are sick outside of working hours because there is not much veterinary clinic that open for 24 hours. So the owners should be capable of giving immediate response to their dogs. Therefore, a system is needed to help this problem using Modified K-Nearest Neighbor (MK-NN) algorithm, to help the owner getting their dog diagnosed and giving immediate response. The system is implemented using Java programming language. There are 10 types of the diseases with 46 clinical symptoms. Based on the accuracy test, the maximum average of accuracy obtained is 96.6% with k=2.